Rekonstrukcja antropologiczno-demograficzna XIII-wiecznej populacji z grodziska Raciąż (pow. tucholski) - Łuczak, Bogdan (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
The basis for the analysis was provided by bone materials dating back to second half of 13th century from a cemetery near the old town of Raciąż. Complete excavation included 67 persons, in this number 19 men, 14 women, and 34 children. The study was aimed at anthropological-demographic reconstruction of the local medieval population at Raciąż. This approach was possible owing to full exploration of the cemetery and strictly defined period during which it was used. Demographic analysis allowed to state that there appeared strong selection pressures in the examined human sample. These concerned mainly children and grown up people in reproduction stage. The discovered structure of the dying age is characteristic for majority of non-maltusian populations. The average family size in the examined local group was fixed at 7 to 5 persons. In this number there were distinguished two persons with parental status, 4 to 5 children, and one person with grandfather’s or grandmother’s status. An average number of the permanent town’s inhabitants at the given moment of time was estimated at 37 people. Anthropological analysis points at ethnogenetic connections between the analyzed population and north-west group (a considerable proportion of the Nordic component). Simultaneously there is observed a considerable portion of admixtues of the yellow race (especially hill element - q) in the racial composition. They were characteristic for the then Polish populations. As regards physical development, there prevailed among Raciąż population medium-size and tall type persons. It is also interesting that among tall persons women prevail. This fact may testify that the level of widely-understood living conditions was not favourable enough for the population. Such situation is usually manifested by a certain decrease in men’s height of body. The assessment of state of health was performed from the point of view of paleopathological changes in bones. It was discovered that most common were diseases in masticatory system and diseases of inflammation type e.g. arthritis chronica. Large occurence of the latter in mature age may testify that living conditions of this population were connected with a big burden of hard manual work.